2007
DOI: 10.5194/npg-14-395-2007
|View full text |Cite
|
Sign up to set email alerts
|

Merging particle filter for sequential data assimilation

Abstract: Abstract.A new filtering technique for sequential data assimilation, the merging particle filter (MPF), is proposed. The MPF is devised to avoid the degeneration problem, which is inevitable in the particle filter (PF), without prohibitive computational cost. In addition, it is applicable to cases in which a nonlinear relationship exists between a state and observed data where the application of the ensemble Kalman filter (EnKF) is not effectual. In the MPF, the filtering procedure is performed based on sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 24 publications
0
83
0
1
Order By: Relevance
“…This problem has been studied before by Nakano et al, (2007), and we use similar model parameters. They showed that tens of thousands of particles were needed with the standard particle filter with resampling for the result that we are able to achieve with 20 particles with the new method.…”
Section: Almost Equal Weightsmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem has been studied before by Nakano et al, (2007), and we use similar model parameters. They showed that tens of thousands of particles were needed with the standard particle filter with resampling for the result that we are able to achieve with 20 particles with the new method.…”
Section: Almost Equal Weightsmentioning
confidence: 99%
“…One tends to need a few hundred particles to solve this problem with the standard particle filter (Nakano et al, 2007).…”
Section: Application To the Lorenz-63 Modelmentioning
confidence: 99%
“…Recently there has been growing interest in particle filtering methods in particular, as these methods are better able to capture the nonlinearity inherent in many geophysical systems [e.g., the merging particle filter of Nakano et al (2007), the equivalent-weights filter of Ades and van Leeuwen (2013), and the implicit particle filter (Morzfeld et al 2012)]. At the same time, particle filters also tend to suffer from the ''curse of dimensionality'' where the required ensemble size grows very rapidly as the dimension increases.…”
Section: Introductionmentioning
confidence: 99%
“…A challenging example for a particle filter is the 40-variable Lorenz 1995 model (Lorenz, 1995), which for the settings given below typically needs tens of thousands of particles (Nakano et al, 2007). The model equations are given by: The end point of that run was used as the initial condition for the data assimilation experiment.…”
Section: Application To the Lorenz-95 Modelmentioning
confidence: 99%